Detection of Plasmodium falciparum DNA in saliva samples stored at room temperature: potential for a non-invasive saliva-based diagnostic test for malaria - Mfuh, Kenji O. (Malar J, 2017)
BACKGROUND: Current malaria diagnostic methods require blood collection, that may be associated with pain and the risk of transmitting blood-borne pathogens, and often create poor compliance when repeated sampling is needed. On the other hand, the collection of saliva is minimally invasive; but saliva has not been widely used for the diagnosis of malaria. The aim of this study was to evaluate the diagnostic performance of saliva collected and stored at room temperature using the OMNIgene(®)•ORAL kit for diagnosing Plasmodium falciparum malaria. METHODS: Paired blood and saliva samples were collected from 222 febrile patients in Cameroon. Saliva samples were collected using the OMNIgene(®)•ORAL (OM-501) kit and stored at room temperature for up to 13 months. Thick blood film microscopy (TFM) was used to detect P. falciparum blood-stage parasites in blood. Detection of P. falciparum DNA in blood and saliva was based on amplification of the multi-copy 18 s rRNA gene using the nested-polymerase chain reaction (nPCR). RESULTS: Prevalence of malaria detected by TFM, nPCR-saliva and nPCR-blood was 22, 29, and 35%, respectively. Using TFM as the gold standard, the sensitivity of nPCR-saliva and nPCR-blood in detecting P. falciparum was 95 and 100%, respectively; with corresponding specificities of 93 and 87%. When nPCR-blood was used as gold standard, the sensitivity of nPCR-saliva and microscopy was 82 and 68%, respectively; whereas, the specificity was 99 and 100%, respectively. Nested PCR-saliva had a very good agreement with both TFM (kappa value 0.8) and blood PCR (kappa value 0.8). At parasitaemia > 10,000 parasites/µl of blood, the sensitivity of nPCR-saliva was 100%. Nested PCR-saliva detected 16 sub-microscopic malaria infections. One year after sample collection, P. falciparum DNA was detected in 80% of saliva samples stored at room temperature. CONCLUSIONS: Saliva can potentially be used as an alternative non-invasive sample for the diagnosis of malaria and the OMNIgene(®)•ORAL kit is effective at transporting and preserving malaria parasite DNA in saliva at room temperature. The technology described in this study for diagnosis of malaria in resource-limited countries adds on to the armamentarium needed for elimination of malaria.